2022
DOI: 10.3390/ma15124326
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Damage Evolution of Multiple-Fractured Rock-like Material Subjected to Compression

Abstract: Multiple compression tests on rock-like samples of pre-existing cracks with different geometries were conducted to investigate the strength properties and crack propagation behavior considering multi-crack interactions. The progressive failure process of the specimens was segmented into four categories and seven coalescence modes were identified due to different crack propagation mechanisms. Ultimately, a mechanical model of the multi-crack rock mass was proposed to investigate the gradual fracture and damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The failure characteristics are presented as the final evolution state of internal microcracks. The failure characteristics contain rich information, such as sample deformation and force transmission path [ 30 , 31 , 32 , 33 ]. Therefore, it is of great significance to analyze them.…”
Section: Mechanical Properties Analysismentioning
confidence: 99%
“…The failure characteristics are presented as the final evolution state of internal microcracks. The failure characteristics contain rich information, such as sample deformation and force transmission path [ 30 , 31 , 32 , 33 ]. Therefore, it is of great significance to analyze them.…”
Section: Mechanical Properties Analysismentioning
confidence: 99%
“…The larger the pre-crack angle (within the range of 30-60 degrees), the higher the compressive strength. Liu et al 52 proposed a mechanical model of multi-crack rock mass, and pointed out that the strength of multi-crack specimens decreases rst and then increases with the increase of crack inclination angle, and decreases with the increase of crack distribution density.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2020) combined with the theory of frost heaving mechanics and fracture mechanics, carried out the freeze-thaw cycle test, and analyzed failure modes and mechanical characteristics of crack growth. Li et al (2022) analyzed the influence of prefabricated crack angles on the mechanical properties and failure modes of coal samples under uniaxial compression. The geometric parameters of the joints in the rock mass (such as the occurrence, length, roughness, connectivity, filling, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Xi et al (2020) indicated that crack initiation and propagation will occur when the stress is far less than the compressive strength of the rock for granite specimens with prefabricated cracks. Liu et al (2022) proposed a mechanical model of multi-cracked rock masses and noted that the strength of multi-cracked specimens decreases first and then increases with the increase in the crack inclination angle. Tiwari and Rao (2006) studied the influence of joint morphology on strain hardening and softening and the plastic behavior of rock masses with triaxial and true triaxial compression tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation